A Typical Bilateral Atrial Myxoma: A Case Report - Zhenghua Xiao; Wei Meng; Da Zhu; Eryong Zhang (Case Reports in Cardiology)
Myxoma is a rare type of tumor which have an incidence of 0.0017% among the general population. Cardiac myxomas which arise from two different heart chambers is even extremely rare; we herein report a unique case of male patient with bilateral myxoma.